Simple bone cyst presenting as an incidental finding in pretreatment orthodontic radiograph: A case report - Salini G Sudha; Sunila Thomas; Vivek Velayudhan Nair (Wolters Kluwer Medknow Publications, 2017)
Pretreatment radiographs, especially panoramic and lateral cephalometric are routinely used as an aid in orthodontic diagnosis and treatment planning. Sometimes abnormalities may be detected as incidental findings in such radiographs that require medical or odontological management. Simple bone cyst is an uncommon lesion mostly occurring in young individuals; it is often asymptomatic and accidently discovered during routine radiological examination. Mostly the pathology presents as a unilocular radiolucency in the mandible between canine and third molar. A definite diagnosis is invariably achieved during surgery as it presents as an empty cavity without lining. We present a case of a simple bone cyst of the body of mandible identified during routine pretreatment orthodontic radiograph.